2017
DOI: 10.1016/j.smallrumres.2016.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Is cross-breeding with indigenous sheep breeds an option for climate-smart agriculture?

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights: This study compared indigenous Mongo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“… Karugia et al (2001) concluded that crossbreeding of cattle had a positive effect on the Kenyan economy and social welfare, although they speculated that the introduction of exotic genes may have not been beneficial at farm level, because improved animal productivity also involved accrued input costs. By contrast, Hegde (2018) reported positive economic impacts of crossbreeding for Indian cattle farmers, with the number of above-poverty-line families increasing by 262% over a ten-year period. In Senegal, Marshall et al (2017) found that under good management, 50% indigenous Zebu by Bos taurus crossbreds for dairy production provided greater net economic benefits to households than did alternative options involving pure indigenous, highly introgressed (with Bos Taurus) or alternative crosses.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… Karugia et al (2001) concluded that crossbreeding of cattle had a positive effect on the Kenyan economy and social welfare, although they speculated that the introduction of exotic genes may have not been beneficial at farm level, because improved animal productivity also involved accrued input costs. By contrast, Hegde (2018) reported positive economic impacts of crossbreeding for Indian cattle farmers, with the number of above-poverty-line families increasing by 262% over a ten-year period. In Senegal, Marshall et al (2017) found that under good management, 50% indigenous Zebu by Bos taurus crossbreds for dairy production provided greater net economic benefits to households than did alternative options involving pure indigenous, highly introgressed (with Bos Taurus) or alternative crosses.…”
Section: Discussionmentioning
confidence: 92%
“…As a consequence, national livestock authorities in developing countries frequently integrate the extensive use of exotic livestock in their development strategies aiming at increasing the productivity of their livestock production systems (see for instance DAPH, 2010 ; GOI, 2013 ; Shapiro et al, 2015 , 2017 ). Abundant literature documents the theoretical and practical impacts of crossbreeding and breed replacement at the local level ( Galukande et al, 2013 ; Getachew et al, 2016 ; Roschinsky et al, 2015 ; Wilkes et al, 2017 ). Various studies have shown that in appropriate production environments, milk yield of crossbred cattle can be 2 to 2.6 times greater than of pure indigenous breeds, with associated increases in farmers’ income ( Galukande et al, 2013 ; Hegde, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐breeding highly selected breeds with indigenous breeds may offer adaptation benefits in some situations, although its effectiveness as an adaptation appears dependent on context (Moore & Ghahramani, 2014 ; Wilkes et al, 2017 ). There is some scope for genetic improvement in animals to increase tolerance to heat stress, such as making use of the slick hair gene in cattle (Ortiz‐Colón et al, 2018 ) or the naked neck gene in poultry (Nawab et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, most examples of those adaptations also reduced GHG emissions, and some were transformational, such as the efforts to redefine cities with 'living infrastructure' 77 . In the case of food security, many adaptations to farm-level practices have been shown to benefit low-income populations or marginalized ethnic groups [78][79][80][81][82] , and many of these responses have not meaningfully increased GHG emissions [83][84][85] . For example, conservation agriculture in India resulted in increased yields and reduction in GHG emissions 84 .…”
Section: Adaptation Outcomes By Rkrmentioning
confidence: 99%